Reducción de la sobrecarga antigénica mediante la realización de la prueba cruzada mayor en fase salina cuando se presentan solicitudes transfusionales de urgencia, empleando las muestras de sangre de los pacientes atendidos en el servicio de emergencia del h.p.g.d.r. durante el periodo julio a noviembre del 2012 - Tapia Armendáriz, Jessica Estefanía (2013)
The transfuctional security measures are aimed to provide the patient the precise type of blood and thus avoid the acute hemolytic reaction, that is to say ensure compatibility between donor and receiver. For ensure a good compatibility is of vital importance perform tests to identify the absence or presence of unexpected or irregulars antibodies Completes the test battery with the call test crusade test or compatibility test, the same consists of 3 phases: the saline phase, liss phase and Coombs phase each of these phases has a specific, thorough procedure in which the health professional must work accurately and conscious